Anal Cancer Precursor Lesions in HIV-Infected Persons: Tissue Human Papillomavirus Type Distribution and Impact on Treatment Response. Issue 5 (May 2019) - Kobayashi, Takaaki; Sigel, Keith; Kalir, Tamara; MacLeod, Iain J.; Liu, Yuxin; Gaisa, Michael
Abstract : BACKGROUND: Data on tissue distribution of human papillomavirus types in anal high-grade squamous intraepithelial lesions are limited and the impact on treatment outcomes poorly understood. OBJECTIVE: We aimed to investigate potential predictors of treatment failure after electrocautery ablation, including human papillomavirus type(s) isolated from index lesions. DESIGN: This was a retrospective cohort study. SETTINGS: The study was conducted at a tertiary academic referral center in New York City. PATIENTS: Seventy-nine HIV-infected patients with a diagnosis of anal high-grade squamous intraepithelial lesions between January 2009 and December 2012 were included, and genomic DNA was extracted from biopsy tissue. MAIN OUTCOME MEASURES: The prevalence of human papillomavirus types in index lesions and surveillance biopsies after electrocautery ablation were analyzed to evaluate treatment response. RESULTS: Of 79 anal high-grade squamous intraepithelial lesions, 71 (90%) tested positive for ≥1 human papillomavirus type; 8 (10%) had no human papillomavirus detected. The most common type was 16 (39%), followed by 33 (15%). Human papillomavirus type 18 was seen in 3%. Sixty-one patients (77%) underwent electrocautery ablation and had subsequent surveillance biopsies. Surveillance biopsies yielded benign findings or low-grade squamous intraepithelial lesions in 31 (51%) of 61 and recurrent high-grade squamous intraepithelial lesions in 30 (49%) of 61 patients (mean follow-up: 35 mo). Ablation response did not differ significantly based on baseline demographics, smoking history, history of anogenital warts, mean CD4 + T-cell count, antiretroviral-therapy use, and HIV viral load (<50 copies/mL). The recurrence of high-grade lesions was not significantly associated with high-risk human papillomavirus types detected in index lesions. LIMITATIONS: Human papillomavirus genotyping in surveillance biopsies was not performed. CONCLUSIONS: Anal high-grade squamous intraepithelial lesions in HIV-infected patients contain a wide range of human papillomavirus types, and individual lesions commonly harbor multiple types concomitantly. Recurrence of anal high-grade squamous intraepithelial lesions after electrocautery ablation occurs frequently and is not affected by high-risk human papillomavirus types. See Video Abstract at http://links.lww.com/DCR/A833 .